BIOLOGICAL EFFECTIVENESS OF HERBICIDES USED IN COMBINATION WITH MUNG BEAN PLANTING TO CONTROL WILD WEEDS - Sattorov Shokhimardon Khushmamatovich; Abdillayev Marat Ibodillayevich; Usmonov Muhriddin Mukhtor uglu; Alamuratov Rayimjon Abdimurot oglu (Modern American Journals, 2025)
In the article, the types, amount, damage of annual and perennial weeds found in fields planted with mung-bean crops in the Tashkent region, as well as herbicides used along with planting Stomp 33% emulsion concentration - 4,0 l/h 89,7% on annual weeds, Shansgard suspension concentration 500 g/l shut up It was reported that 88,2% biological efficiency was achieved on annual weeds when used at rates of - 4,0 l/ha.
Keywords: Mung-bean, annual and perennial weeds, dicotyledonous, cereal, distribution, harmfulness, quantity, herbicide, emulsion concentration, suspension concentration, biological efficiency.